2023
DOI: 10.1002/adfm.202304674
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Stiffness and Particle Properties Influence Cellular Uptake of Nanoparticles and Viruses from the Ventral Side

Jonah L. Voigt,
Jens Timmer,
Federica Pennarola
et al.

Abstract: It is a long‐standing challenge to exploit cellular uptake mechanisms to deliver desired cargo into cells, for example, specific drugs or gene editing techniques. This study introduces a bioinspired material approach where nanoparticles are presented at the ventral side of cells adhering to engineered extracellular matrices. The effect of matrix stiffness on cell adhesion and mechanics, as well as on particle internalization by clathrin‐mediated endocytosis (CME), is investigated for varying particle size and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Activation of clathrin-mediated endocytosis reduced the effect of substrate stiffness on particle uptake. Myosin II is important for regulation of the effect of substrate stiffness on particle uptake [ 179 ] HeLa (human cervical cancer); HCT-8 (human large intestine cancer) Polystyrene nanoparticles 100 NA NA ECM stiffness Cellular uptake of nanoparticles decreases on a per-cell-area basis but increases on a per-cell basis with increasing gel stiffness [ 177 ] AsPC-1 (human pancreatic adenocarcinoma); MDA-MB-231 (human breast adenocarcinoma) Polystyrene beads 800; 2400 NA; NA NA; NA ECM stiffness A wave-like (“meandering”) dependence of cell uptake on the substrate stiffness [ 213 ] bEnd.3 (mouse brain endothelial) cells Polystyrene nanoparticles Plain particles 108.07 ± 1.12; RGD-functionalized 114.67 ± 1.53; Scrambled RGD-functionalized 110.33 ± 0.86 − 48.33 ± 0.91; − 36.17 ± 0.61; − 36.13 ± 0.84 0.005 ± 0.003; 0.07 ± 0.02; 0.04 ± 0.02 ECM stiffness Higher stiffness promoted RGD-functionalized nanoparticles uptake by the cells [ 178 ] BeWo b30 cells (choriocarcinoma cell line) PEGylated DOPC liposomes Plain liposomes 48.8 ± 0.3; CSA-conjugated liposomes 93.7 ± 1.2 11.48 ± 4.36; − 25.5 ± 2.81 0.19 ± 0.01; 0.25 ± 0.01 Shear stress Shear stress promoted the cell uptake of liposomes [ 183 ] HUVECs Gold nanoparticles; Liposomes Gold nanoparticles untargeted PEG (5 kDa)-coated; 100; Gold nanoparticles targeted PEG (5 kDa)-coated; UEA-1-modified; ...…”
Section: Effects Of Mechanical Stimuli On Nanoparticle Uptake By Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…Activation of clathrin-mediated endocytosis reduced the effect of substrate stiffness on particle uptake. Myosin II is important for regulation of the effect of substrate stiffness on particle uptake [ 179 ] HeLa (human cervical cancer); HCT-8 (human large intestine cancer) Polystyrene nanoparticles 100 NA NA ECM stiffness Cellular uptake of nanoparticles decreases on a per-cell-area basis but increases on a per-cell basis with increasing gel stiffness [ 177 ] AsPC-1 (human pancreatic adenocarcinoma); MDA-MB-231 (human breast adenocarcinoma) Polystyrene beads 800; 2400 NA; NA NA; NA ECM stiffness A wave-like (“meandering”) dependence of cell uptake on the substrate stiffness [ 213 ] bEnd.3 (mouse brain endothelial) cells Polystyrene nanoparticles Plain particles 108.07 ± 1.12; RGD-functionalized 114.67 ± 1.53; Scrambled RGD-functionalized 110.33 ± 0.86 − 48.33 ± 0.91; − 36.17 ± 0.61; − 36.13 ± 0.84 0.005 ± 0.003; 0.07 ± 0.02; 0.04 ± 0.02 ECM stiffness Higher stiffness promoted RGD-functionalized nanoparticles uptake by the cells [ 178 ] BeWo b30 cells (choriocarcinoma cell line) PEGylated DOPC liposomes Plain liposomes 48.8 ± 0.3; CSA-conjugated liposomes 93.7 ± 1.2 11.48 ± 4.36; − 25.5 ± 2.81 0.19 ± 0.01; 0.25 ± 0.01 Shear stress Shear stress promoted the cell uptake of liposomes [ 183 ] HUVECs Gold nanoparticles; Liposomes Gold nanoparticles untargeted PEG (5 kDa)-coated; 100; Gold nanoparticles targeted PEG (5 kDa)-coated; UEA-1-modified; ...…”
Section: Effects Of Mechanical Stimuli On Nanoparticle Uptake By Cellsmentioning
confidence: 99%
“…Other research has suggested that the stiffness of the substrate influences both cell adhesion and particle internalization. Softer substrates appear to enhance the levels of particle uptake [ 27 , 179 ]. One can definitely say that cell type predisposes response of cells to external stiffness (Table 2 ).…”
Section: Effects Of Mechanical Stimuli On Nanoparticle Uptake By Cellsmentioning
confidence: 99%
See 3 more Smart Citations